TERMS OF TIME IN THE KARAKALPAK LANGUAGE - Bekbosinova Zamira Qidirbaevna (International Journal of Literature and Language Studies, 2026)
The concept of measure is encountered in every sphere of human life. Therefore, the objective nature of number, its understanding, and its occurrence in human consciousness are examined in works related to mathematics, philosophy, linguistics, and logic. This article discusses the study of time measurement categories, time measurement terms, current measurement terms, and time measurements used by Turkic-speaking peoples, and provides examples from literary works.